2018
DOI: 10.3389/fimmu.2018.01094
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Role of RNA-Binding Proteins in Gene Expression in the Immune System

Abstract: Fighting external pathogens requires an ever-changing immune system that relies on tight regulation of gene expression. Transcriptional control is the first step to build efficient responses while preventing immunodeficiencies and autoimmunity. Post-transcriptional regulation of RNA editing, location, stability, and translation are the other key steps for final gene expression, and they are all controlled by RNA-binding proteins (RBPs). Nowadays we have a deep understanding of how transcription factors control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 221 publications
(221 reference statements)
0
58
1
1
Order By: Relevance
“…However, key molecular players remain elusive. mRNA biogenesis and stability/degradation have been shown to modulate numerous cellular processes involved in cancer, inflammation, cell death, proliferation etc Our previous study has shown that IL‐10 (anti‐inflammatory cytokine)‐mediated suppression of human antigen R (HuR, an mRNA stabilizing protein) attenuates MI‐induced cardiac remodeling . In this perspective, the influence of diabetic milieu on tissue macrophage and fibroblasts cross talk via exosome transfer of HuR and its implications on cardiac remodeling has never been studied.…”
Section: Discussionmentioning
confidence: 99%
“…However, key molecular players remain elusive. mRNA biogenesis and stability/degradation have been shown to modulate numerous cellular processes involved in cancer, inflammation, cell death, proliferation etc Our previous study has shown that IL‐10 (anti‐inflammatory cytokine)‐mediated suppression of human antigen R (HuR, an mRNA stabilizing protein) attenuates MI‐induced cardiac remodeling . In this perspective, the influence of diabetic milieu on tissue macrophage and fibroblasts cross talk via exosome transfer of HuR and its implications on cardiac remodeling has never been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Differentiation of Tfh cells is regulated by extracellular signals from antigens; stimulatory or inhibitory coreceptors including ICOS, PD-1, CD40L, and OX40; and cytokines including IL-6 and IL-21 (18). Downstream of these factors, dozens of transcription factors, RNA-binding proteins, and microRNAs have been reported to control the gene expression specification for Tfh cell differentiation (19)(20)(21). Among these, the transcription factor BCL6 is considered to constitute a master regulator due to the fact that it is necessary with regard to driving the differentiation of Tfh cells (19,22).…”
Section: Introductionmentioning
confidence: 99%
“…5,7,8 These proteins act cooperatively for the maintenance of self-renewal and differentiation of SC and adult tissues, together or independently. 6,13,14 Thus, by controlling these mechanisms, Musashi proteins act for the maintenance of self-renewal and differentiation of SC and adult tissues, together or independently. Both have two RNA-recognition motifs, das Chagas and Baroni contributed equally to this work.…”
Section: Introduction: the Rna Binding-protein Musashimentioning
confidence: 99%
“…12 Msi1 and Msi2 bind to the 3'-UTR of several target mRNAs increasing or attenuating their expression either during pre-mRNA processing or alternative splicing, interfering with their transport into the cytoplasm, or affecting the stability and turnover of the target gene itself. 6,13,14 Thus, by controlling these mechanisms, Musashi proteins act for the maintenance of self-renewal and differentiation of SC and adult tissues, together or independently. [8][9][10] Both proteins are considered biomarkers of stemness and are expressed in diverse cell types at different levels of tissue differentiation.…”
mentioning
confidence: 99%